ANALISIS EFISIENSI DAN PENGARUHNYA TERHADAP STOCK RETURN PADA BANK BUMN, BANK SWASTA NASIONAL, DAN BANK ASING DI INDONESIA TAHUN 2010-2018 - Nintagi Happy Imansari (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this studi are to measure the level of efficiency of state-owned banks, private banks and foreign banks in Indonesia in 2010-2018. In addition, it was also to find out the effect of the level of efficiency on the stock returns of banks owned by SOEs, private banks and foreign banks in Indonesia in 2010-2018. The method used in this study consists of 2 methods: for analyzing bank efficiency measurements using the non-parametric Data Envelopment Analysis (DEA) method and analyzing the factors that affect efficiency using the panel data regression model. The results of this study indicate that the measurement of bank efficiency by using input-oriented DEA, the level of efficiency of 10 foreign commercial banks, national private companies and BUMN listed on the Indonesia Stock Exchange in the period 2010-2018 the majority of banks run their operations efficiently. In addition, the results of testing the independent variable on the dependent variable can be analyzed that the efficiency variable has a positive coefficient and has a significant effect on stock returns. Keywords: Bank Efficiency, Data Envelopment Analysis (DEA), Stock Return